Effektiv materialförsörjning i en försörjningskedja hos ett MTO-företag : En fallstudie på ABB Components i Ludvika - Krönander, John; Åsling, Mattias (2014)
The growing competition between companies have led to their supply chains becoming a means for obtaining competitive advantages. The supply chains have become more complex because of an increased focus on lower costs, a shorter life cycle on products and an increased demand. This increased complexity have created a need to identify problems in the supply chain. Furthermore, as the competition have increased, the lead time have become an important parameter for companies. In a Make-to-Order (MTO) company a short lead time can be the deciding factor if they are to be the order winner. The lead time from the supplier is major contributing factor to the total lead time and inventory are often used to reduce its impact. Inventory can however be disadvantageous as it ties up capital and is a source of waste.ABB Components in Ludvika is a MTO company and a part of Power Products which is a division in ABB Ltd and are the world’s largest manufacturer of bushings. ABB Composites in Piteå are also a part of the division Power Products and produce insulators which is a component of the bushings. The procurement of insulators for one of Components products is based on a forecast due to long lead times from Composites and Components maintains a large inventory of insulators. Components has an ambition to make the supply of material more efficient to obtain shorter lead times and reduced inventory. This study was of a dual nature in which the first part had the purpose of identifying actions that can improve the efficiency of a supply chain in an MTO company. This was done through a process mapping of Components supply chain where factors affecting lead time and inventory were identified. From the process mapping an action with the potential to shorten the lead time and inventory levels were identified that formed the basis for the second phase of the study.This study shows that uncertainty in forecasts have a large effect on both the lead time through the amplification of the lead time gap and higher inventory levels. In ...